2019
DOI: 10.1186/s12866-019-1470-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of methicillin-resistant Staphylococcus aureus strain SO-1977 from Sudan

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) is known as a leading cause of morbidity and mortality. Investigation of the MRSA’s virulence and resistance mechanisms is a continuing concern toward controlling such burdens through using high throughput whole Genome Sequencing (WGS) and molecular diagnostic assays. The objective of the present study is to perform whole-genome sequencing of MRSA isolated from Sudan using Illumina Next Generation Sequencing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The isolates distributed in the three branches with those from Japan (LC508802), Nigeria (MN606199), Germany (MF664194), Italy (MN811085), Ethiopia (MK217496), Iraq (MN555444), Pakistan (MN611106), Bangladesh (MN611246), Egypt (MN556575), China (MN652637), India (MK165143) and USA (MF385261). The current results agree with previouly reported study in Sudan by Mohamed et al that found genetic similarity in genomic sequence analyses of different S.aureus strains in the world in relation with isolated strains [26]. Similar to the current study results, Raed et al indicated that genetic dimension between Iraq and the isolates of the world is extremely relative, and 16s rRNA analysis is considered a good discrimination approach for distinguishing unrelated isolates [27].…”
Section: Discussionsupporting
confidence: 92%
“…The isolates distributed in the three branches with those from Japan (LC508802), Nigeria (MN606199), Germany (MF664194), Italy (MN811085), Ethiopia (MK217496), Iraq (MN555444), Pakistan (MN611106), Bangladesh (MN611246), Egypt (MN556575), China (MN652637), India (MK165143) and USA (MF385261). The current results agree with previouly reported study in Sudan by Mohamed et al that found genetic similarity in genomic sequence analyses of different S.aureus strains in the world in relation with isolated strains [26]. Similar to the current study results, Raed et al indicated that genetic dimension between Iraq and the isolates of the world is extremely relative, and 16s rRNA analysis is considered a good discrimination approach for distinguishing unrelated isolates [27].…”
Section: Discussionsupporting
confidence: 92%
“…The isolates distributed in the three branches with those from Japan (LC508802), Nigeria (MN606199), Germany (MF664194), Italy (MN811085), Ethiopia (MK217496), Iraq (MN555444), Pakistan (MN611106), Bangladesh (MN611246), Egypt (MN556575), China (MN652637), India (MK165143) and USA (MF385261). The current results agree with previously reported study in Sudan by Mohamed et al [ 28 ] that found genetic similarity in genomic sequence analyses of different S. aureus strains in the world in relation with isolated strains. Similar to the current study results, Raed et al .…”
Section: Main Textsupporting
confidence: 93%
“…Many of these established techniques are costly and time-consuming, and the discriminatory abilities of these techniques are also different (Du et al 2011 ). However, the spa typing method has been considered as a rapid and inexpensive method for genotyping and it provides high discriminating power than other typing methods (Shittu et al 2011 ; O’Hara et al 2016 ; Goudarzi et al 2017 ; Ali et al 2019 ; Rezai et al 2019 ; Kareem et al 2020 ). Both phenotypic and molecular typing methods have been used widely to detect and differentiate several MRSA strains, but these techniques have certain limitations in infection control and investigating the nosocomial transmission as these techniques provide low resolution and more time-consuming.…”
Section: Introductionmentioning
confidence: 99%